Mytilicola orientalis Mori, Crassostrea gigas Thunberg's parasite, in the basin of Marennes Oleron : impact on the condition and the biochemical composition of oysters during rearing - Deslous-paoli, Jean-marc (ICES-CIEM CM 1981 / K:29, 1981)
Crassostrea gigas Thunberg's infestation by Mytilicola orientalis. Mori in 1979 in the basin of" Marennes-Oléron presents two maxima, one during spring, the other during autumn. The parasites have infested until 64 %of bred oysters. The intensity of infestation la weak (93.5 %of oysters are infested by lass than six females) and depend on the hosts'size. By this fact, slgnificant impact appears only in spring and in winter. A middle infestation of more than three M. orientalis females seems to induce a significant decrease of rates of carbohydrates and of glycogen L'infestation de Crassostrea gigas Thunberg par Mytilicola orienalis Mori en 1979 dans le bassin de Marennes-Oléron, présente deux maxima, l'un au printemps, l'autre en automne. Les parasites ont infesté jusqu'à 64% des huîtres mises en élevage. L'intensité d'infestation est faible (93,5% des huîtres sont infestées par moins de six femelles) et dépend de la taille des hôtes. De ce fait, il n'apparaît d'impact significatif sur l'index de condition qu'au printemps et en hiver. Une infestation moyenne de plus de trois femelles de M. orientalis semble induire une réduction significative des taux de glucides totaux et de glycogène.